2017
DOI: 10.1002/jtr.2110
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new definition for “visiting friends and relatives”

Abstract: “Visiting friends and relatives” (VFR) is a tourism term used in academic and practitioner vernacular that refers to a substantial amount of activity and is yet commonly disregarded. This paper builds on previous literature that has demonstrated how a lack of understanding of what VFR encompasses facilitates the phenomenon to be undervalued and misunderstood. Without a clear conceptual definition, VFR continues to be presented with inconsistent and conflicting parameters, which creates discursive confusion rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
(62 reference statements)
2
37
0
1
Order By: Relevance
“…In total, 2,201 responses were collected with 1,792 (81.4%) having hosted in the last 3 years. “Hosting” was defined for participants as when “your friends or relatives visited the GTA and spent time with you.” Consistent with the previous discussion in the Literature Review (Munoz et al, 2017; Young et al, 2007), these visitors could have stayed in the hosts' homes or elsewhere in the area (e.g., hotel or the home of a different friend or relative). The survey questions focused on characteristics of the most recent hosting experience within the past 3 years, including guest characteristics (e.g., party size and make up, origin, friends and/or relatives, trip purpose, first time/repeat visitors, and accommodation use), season and duration of visit, host encouragement for the visit, host participation in activities, and host demographics.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In total, 2,201 responses were collected with 1,792 (81.4%) having hosted in the last 3 years. “Hosting” was defined for participants as when “your friends or relatives visited the GTA and spent time with you.” Consistent with the previous discussion in the Literature Review (Munoz et al, 2017; Young et al, 2007), these visitors could have stayed in the hosts' homes or elsewhere in the area (e.g., hotel or the home of a different friend or relative). The survey questions focused on characteristics of the most recent hosting experience within the past 3 years, including guest characteristics (e.g., party size and make up, origin, friends and/or relatives, trip purpose, first time/repeat visitors, and accommodation use), season and duration of visit, host encouragement for the visit, host participation in activities, and host demographics.…”
Section: Methodssupporting
confidence: 74%
“…Paid), identifying three groups of which three can be considered a type of VFR (VFR/FR, VFR/Paid, Pleasure/FR). Munoz, Griffin, and Humbracht (2017) proposed the concept of mobility influenced by hosts more broadly, within which VFR is positioned as one form “that involves a face‐to‐face interaction between host and visitor [who knew each other previously] within the destination” (p. 482). This more holistic conceptualisation lays the foundation to identify the many diverse types of VFR experiences from the guest or host perspective (Backer & Lynch, 2017), ranging from obligatory familial functions (e.g., weddings), to multi‐destination trips that involve a VFR stop, to a convention visitor catching up for a drink with an old college friend.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffin (2013) argues that the desire to visit friends and relatives is a fundamental driver for a large part of global tourism. Munoz et al (2017) have stated that economic benefits reflecting on visiting friends and relative's community are consequently affecting social and cultural development. This type of tourist is using the time to go to festivals, see attractions, neighbourhoods and therefore indirectly improving the quality of life for the residents making the locality more attractive and authentic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The definition of VFR tourism by Larsen et al (2007) also emphasises the guests' perspective and thus may not cover all situations where VFR tourism occurs. More recently, Munoz, Griffin and Humbracht (2017) suggested that VFR can be defined as a form of mobility influenced by a host that involves a face-to-face interaction between host and visitor within the destination. Their definition takes into account the limitations of previous definitions and appears to be inclusive of most situations where VFR occurs.…”
Section: The Concept Of Vfr Tourismmentioning
confidence: 99%